Establishing family physician research networks in South Africa - Robert Mash (South African Family Practice)
Practice-based research networks have been an important strategy in many parts of the world to enable primary care research and involve clinicians. The Stellenbosch University Family Physician Research Network (SUFPREN) was established in 2017 to enable family physicians in clinical practice to engage with practical research that addressed key challenges and enhanced clinical governance. It is a collaboration between academic family physicians at the university and clinical family physicians in the district health services. In this article, the establishment of SUFPREN is described – membership of the network, selection of research questions, roles in the research process, communication and coordination, involvement of the Department of Health, types of questions and methods, data management, dissemination of findings and funding. The initial work of SUFPREN is described and a vision for future family physician research networks in South Africa is defined.